The forgotten recipe [large type] - Clipston, Amy (Clipston, Amy. Amish heirloom novel, 2016)
"After losing her beloved fiancé, Veronica Fisher takes solace in opening a bake stand to sell creations made from her mother's recipe, and soon, a regular visitor to her stand begins to gladden her heart"--